ANALISIS KINERJA KEUANGAN TERHADAP HARGA SAHAM LQ 45 DI BEI - Cicih Ratnasih (Jurnal Manajemen FE-UB, 2014)
The method used in this research is descriptive method with the help of assaciative analrsis lools Eviews 8 version. This research was conducted by using secandary data collected from the publication of the Indonesia Stock Evchanze. The population in this SilIdy is a compaily that is included in 1.045 in hidonesia Stock Exchange from 2009 to 2013 vears. The sampling method used purposive sampling technique. In accordance with the criteria ohtained a total sample of six companies during the observation period of 5 years. So that the sample is as much as 30 samples. The analysis technique used is multiple regression analysis and hypothesis testing using t test partial, F test simultaneously with the le•el of significance of 5% and the coefficient of determination test. Regression analvsis showed that partially Price to Book Value (PB19 and Earning Per Share (EPS) have a significant effect on stock prices. Simultaneously, the Price to Book Value (PBV) and Earning Per Share (EPS) hare a significant effect 011 stock prices and have the effect of 96.54% of the share price. while the remaining 3.46% is ii?fluenced by other .factors not included in the research model.   Keywords : Price to Book Value (PBr). Earning Per Share (EPS), and Stock Price